161k views
1 vote
Solve for x:
5x - 5 = 9x + 3

2 Answers

6 votes

Answer:

Add

5

5

5

to both sides of the equation

5

5

=

9

+

3

5x-5=9x+3

5x−5=9x+3

5

5

+

5

=

9

+

3

+

5

5x-5+{\color{#c92786}{5}}=9x+3+{\color{#c92786}{5}}

5x−5+5=9x+3+5

2

Simplify

Add the numbers

Add the numbers

again

5

=

9

+

8

5x=9x+8

5x=9x+8

3

Subtract

9

9x

9x

from both sides of the equation

5

=

9

+

8

5x=9x+8

5x=9x+8

5

9

=

9

+

8

9

5x{\color{#c92786}{-9x}}=9x+8{\color{#c92786}{-9x}}

5x−9x=9x+8−9x

4

Simplify

Combine like terms

Combine like terms

again

4

=

8

-4x=8

−4x=8

5

Divide both sides of the equation by the same term

4

=

8

-4x=8

−4x=8

4

4

=

8

4

−4−4x​=−48​

6

Simplify

Cancel terms that are in both the numerator and denominator

Divide the numbers

= − 2

x=-2

x=−2

Solution

= − 2

Explanation:

User Glen Morse
by
4.7k points
3 votes
X = 2

Simplifying
5x + 5 = 9x + -3

Reorder the terms:
5 + 5x = 9x + -3

Reorder the terms:
5 + 5x = -3 + 9x

Solving
5 + 5x = -3 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
5 + 5x + -9x = -3 + 9x + -9x

Combine like terms: 5x + -9x = -4x
5 + -4x = -3 + 9x + -9x

Combine like terms: 9x + -9x = 0
5 + -4x = -3 + 0
5 + -4x = -3

Add '-5' to each side of the equation.
5 + -5 + -4x = -3 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = -3 + -5
-4x = -3 + -5

Combine like terms: -3 + -5 = -8
-4x = -8

Divide each side by '-4'.
x = 2

Simplifying
x = 2
User Patrick Reck
by
4.3k points